Precautionary Measures in The Iraqi Anti-Trafficking Law and Its Evaluation in Islamic Jurisprudence - Karzan Faqikhalil Kareem; Ardawan Mustafa Ismael (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Protecting individuals and maintaining their safety in the face of criminal danger is an essential duty of the state in society to curb the spread of crime by taking precautionary measures aimed at preventing the commission of crime. The Iraqi legislator realized the importance of this, so he issued a special law No. (28) in the year (2012) to prevent the commission of crime. The crime of human trafficking and limiting its spread, as the second and third articles of this law stipulate a set of tasks to achieve the objectives of this law, the purpose of which is to set a policy to prevent and combat human trafficking in Iraq, but the Iraqi legislator was not successful in formulating it, he resorts to the prevention policy Prevention is to limit the commission of a crime after its occurrence by means of precautionary measures, but it has contained shortcomings, shortcomings and defects in terms of precautionary measures, as it needs to be evaluated in the light of Islamic law.